Molecular cloning and expression analysis of three ThERFs involved in the response to waterlogging stress of Taxodium ‘Zhongshanshan406’, and subcellular localization of the gene products - Fan, Wencai; Yang, Ying; Wang, Zhiquan; Yin, Yunlong; Yu, Chaoguang; Shi, Qin; Guo, Jinbo; Xuan, Lei; Hua, Jianfeng (PeerJ, 2018)
As a subfamily of the APETALA 2/ethylene response element binding protein (AP2/EREBP) transcription factor superfamily, the ethylene response factor (ERF) is widely involved in the regulation of growth and response to various abiotic stresses in plants, and has been shown to be the main transcription factor regulating transcription of the genes related to hypoxia and waterlogging stress. In this study, three ThERF genes, with significant differences in expression profile in response to flooding stress, were identified from the transcriptomics data acquired from Taxodium hybrid ‘Zhongshanshan 406’ (T. mucronatum Tenore × T. distichum (L.) Rich) under waterlogging stress: ThERF15, ThERF39 and ThRAP2.3 (GenBank ID: KY463467, KY463468 and KY463470, respectively).The full-length cDNA of each of the three ERFs was obtained using the RACE (rapid amplification cDNA ends) method, and all three were intron-free. Multiple protein sequence alignments indicated that ThERF15, ThERF39 and ThRAP2.3 proteins all had only one AP2-ERF domain and belonged to the ERF subfamily. A transient gene expression assay demonstrated that ThERF15, ThERF39 and ThRAP2.3 were all localized to the nucleus. Real-time quantitative PCR (qPCR) revealed that the expression of ThERF15, ThERF39 and ThRAP2.3 exhibited significant differences, compared with the control, in response to two levels of flooding treatment (half-flooding or total-submergence) of ‘Zhongshanshan 406’. Quantification of ethylene concentration revealed that ethylene was more relevant to the level of expression than the period of flooding treatment. Based on the experimental results above, ThERF15, ThERF39 and ThRAP2.3 were identified as being related to the regulation of downstream flooding- responsive gene expression in ‘Zhongshanshan 406’. ThRAP2.3 is most likely to be a key downstream-response ERF gene to respond to the output of the ethylene signal generated by flooding stress.
Keywords: ThERF genes; Taxodium hybrid ‘Zhongshanshan 406’; Cloning; Subcellular localization; Expression analysis; Ethylene concentration